Clinical Treatment Strategies and Practical Pathways for Chronic Musculoskeletal Disorders Guided by the “Harmony of Tendons and Bones” Theory - LI Jinyu; YUE Jiashu; DENG Bowen; LIU Gang; HUO Luyao; BAI Huizhong; ZHOU Zhuoluo; MU Xiaohong (康复学报)
Chronic musculoskeletal disorders (CMSDs) are a class of chronic and progressive osteoarticular diseases resulting from the combined effects of biological and biomechanical factors, which severely impair patients’ quality of life and impose a substantial socioeconomic burden. Based on classical traditional Chinese medicine (TCM) theory, Professor MU Xiaohong of Dongzhimen Hospital, Beijing University of Chinese Medicine, proposed the “Harmony of Tendons and Bones” theory and applied it in the clinical management of CMSDs. This study elucidates the origins and connotations of the “Harmony of Tendons and Bones” theory, explores the pathogenesis, treatment, and innovative development pathways of CMSDs under this theoretical framework, aiming to provide a theoretical basis and practical support for TCM interventions in CMSDs. The “Harmony of Tendons and Bones” theory, rooted in the Huangdi Neijing (Yellow Emperor’s Inner Canon), emphasizes the mutual coordination of tendons and bones, achieving biomechanical balance and functional integration through the nourishment of meridians and qi-blood. The theory posits that tendon-bone imbalance is the core mechanism underlying the dynamic and static instability of CMSDs; disharmony of meridians and qi-blood is the pathological nexus of tendon-bone imbalance; and deficiencies of the liver, kidney, and spleen are the fundamental causes of qi-blood disharmony. At different stages of disease progression, CMSDs manifest as pathological states of tendon-bone imbalance, malnourishment, and flaccidity or weakness. Therapeutic strategies should adhere to the principles of regulating tendons and correcting bones, emphasizing both tendon and bone, tonifying the liver and kidney, harmonizing qi and blood, and implementing stage-specific and dynamic interventions. A combination of internal therapy, external therapy, surgery, exercise therapy, and modern rehabilitation methods is recommended, with emphasis on the integration of medical treatment and health maintenance, to achieve the therapeutic goals of “utilizing smoothness” and “pursuing balance, ” restore the harmonious state of tendons and bones, improve disease progression, and enhance quality of life. Furthermore, the study proposes multidimensional innovation through equipment upgrading, technological development, and system reconstruction, promoting the deep integration of the “Harmony of Tendons and Bones” theory with industrial and scientific advancements, and providing a continuous source of innovation and momentum for the modernization of TCM in CMSDs management.